Encounters and management of oral conditions at general medical practices in Australia - An-Lun Cheng; Joerg Eberhard; Julie Gordon; Madhan Balasubramanian; Amber Willink; Woosung Sohn; Jennifer Dai; Christopher Harrison (BMC, 2022)
Abstract Background Poor oral health has been widely recognised as an ongoing public health issue. Patients with oral conditions may visit either a general practitioner (GP) or a dental practitioner for management. The aims of this study are to report (i) the GP management rate of oral health conditions by patient and GP demographics, (ii) what specific oral conditions were managed, and (iii) how GPs managed oral conditions. Methods Data from the Bettering the Evaluation and Care of Health study (2006 to 2016 inclusive) were analysed. Descriptive statistics with 95% confidence intervals around point estimates were used to summarise data. Multivariate logistic regression was performed to determine the independent effect of patient and GP characteristics. Results A total of 972,100 GP encounters were included in the dataset, with oral condition-related encounters managed at a rate of 1.19 oral conditions per 100 GP encounters. Patients who were aged 54 years or younger, resided in a socioeconomically disadvantaged area, came from a non-English speaking background or Indigenous background were more likely to have oral conditions managed by GPs. The most commonly reported oral conditions were dental and oral mucosa-related. Over 60% of oral conditions were managed by GPs through prescribed medications. Conclusions This study provided an overview of management of oral conditions by GPs in Australia. Patients from certain vulnerable demographic groups were more likely to attend a GP for management of oral conditions. Common oral conditions and management approaches were identified. The findings of this study contribute to public health and health policy discussions around optimising primary care provision in oral health.